2018
DOI: 10.1021/acs.jafc.8b05062
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS-Based Metabolomics Reveals the Chemical Changes of Polyphenols during High-Temperature Roasting of Large-Leaf Yellow Tea

Abstract: Large-leaf yellow tea (LYT) is made from mature tea leaves with stems and has unique sensory characteristics different from other teas. To study the chemical changes of LYT during processing, samples were collected from each step for quantitative and qualitative analyses by high-performance liquid chromatography and liquid chromatography−mass spectrometry (LC-MS). LC-MS-based nontargeted and targeted metabolomics analyses revealed that the tea sample after roasting was markedly different from samples before ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 32 publications
(59 reference statements)
2
108
0
Order By: Relevance
“…Furthermore, epimerization is another reason for the changes in catechins content in different type tea. some studies have reported that high‐temperature processing induces epimerization of tea catechins, such as 2,3‐ cis (EC, ECG, EGC, and EGCG), to form 2,3‐ trans configurations (C, GC, and GCG; Long et al., 2020; Zhou et al., 2018). Some report that the levels of EGCG, ECG, EC, and EGC were dramatically decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, epimerization is another reason for the changes in catechins content in different type tea. some studies have reported that high‐temperature processing induces epimerization of tea catechins, such as 2,3‐ cis (EC, ECG, EGC, and EGCG), to form 2,3‐ trans configurations (C, GC, and GCG; Long et al., 2020; Zhou et al., 2018). Some report that the levels of EGCG, ECG, EC, and EGC were dramatically decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that evaluation of the secondary metabolomics of tea and the use of chemometric tools, such as principal component analysis (PCA) and linear discriminant analysis (LDA) can help in the exploratory study and classification of tea according to its cultivar, type, and geographical origin (Long et al., 2020; Zhang et al., 2019; Zhou et al., 2018, 2019). However, it is difficult for tea regulatory agencies and research institutions to use this method to distinguish tea types because of its higher technological and skill requirements.…”
Section: Introductionmentioning
confidence: 99%
“…At the A‐ring of flavan‐3‐ols, C 6 and C 8 are reactive carbons that can react with electron accepting compounds and produce many kinds of C 6 or C 8 substituted catechins. A series of N ‐ethyl‐pyrrolidinone substituted flavan‐3‐ols (EPSFs) has been isolated and identified from black, postfermented (dark tea), white, and yellow teas (Dai et al., ; Tanaka, Watarumi, Fujieda, & Kouno, ; Wang et al., ; Zhou et al., ). It is hypothesized that the Strecker degradation product of theanine is involved in the formation of N ‐ethyl‐pyrrolidinone substituted flavan‐3‐ols.…”
Section: Tea Chemistrymentioning
confidence: 99%
“…Recently, EPSFs were also identified from white and ripened pu‐erh teas, the substitution of N ‐ethyl‐2‐pyrrolidinone could be placed at the C 6 or C 8 of EGCG, EC, EGC, and ECG (Cheng et al., ; Wang et al., ; Zhou et al., ). These findings indicated that C 6 and C 8 are very reactive carbons, and then many other types of flavan‐3‐ols derivatives were also found.…”
Section: Tea Chemistrymentioning
confidence: 99%
“…The similar phenomenon was reported in the high temperature treatment of large-leaf yellow tea. 3 No feature signals for FBRFAs or dihydromyricetin were observed from the network. The result validated that the hygrothermal effect was not the reason for generation of FBRFAs or flavan-3-ol C-ring oxidation products in tea leaves.…”
mentioning
confidence: 99%